Nanolithography : the art of fabricating nanoelectronics, nanophotonics and nanobiology devices and systems - Feldman, Martin (Woodhead Publishing series in electronic and optical materials., 2014)
Nanolithography outlines the present state of the art in lithographic techniques, including optical projection in both deep and extreme ultraviolet, electron and ion beams, and imprinting. Emerging technologies are described, including the directed assembly of wafer features, nanostructures and devices, nano-photonics, and nano-fluidics. The goal of this book is to give enough background information to enable researchers to understand and appreciate new developments in nanolithography, and to go on to make advances of his/her own. Topics include: current state of the art in alternative nanolithography technologies in order to cope with the future reduction in size of semiconductor chips to nanoscale dimensions; lithographic techniques, including optical projection, extreme ultraviolet (EUV), nanoimprint, electron beam and ion beam lithography; emerging applications of nanolithography in nanoelectronics, nanophotonics and microfluidics. --